Brentuximab vedotin in relapsed/refractory Hodgkin lymphoma. The Hellenic experience. Issue 1 (20th February 2017) - Angelopoulou, Maria K.; Vassilakopoulos, Theodoros P.; Batsis, Ioannis; Sakellari, Ioanna; Gkirkas, Konstantinos; Pappa, Vasiliki; Giannoulia, Panagiota; Apostolidis, Ioannis; Apostolopoulos, Christos; Roussou, Paraskevi; Panayiotidis, Panayiotis; Dimou, Maria; et al.
Abstract: This retrospective study aimed to describe the Hellenic experience on the use of brentuximab vedotin (BV) in relapsed/refractory (R/R) Hodgkin lymphoma (HL) given within its indication. From June 2011 to April 2015, ninety‐five patients with R/R HL, who received BV in 20 centers from Greece, were analyzed. Their median age was 33 years, and 62% were males. Sixty‐seven patients received BV after autologous stem cell transplantation failure, whereas 28 patients were treated with BV without a prior autologous stem cell transplantation, due to advanced age/comorbidities or chemorefractory disease. The median number of prior treatments was 4 and 44% of the patients were refractory to their most recent therapy. The median number of BV cycles was 8 (range, 2‐16), and the median time to best response was the fourth cycle. Fifty‐seven patients achieved an objective response: twenty‐two (23%), a complete response (CR), and 35 patients (37%), a partial, for an overall response rate of 60%. Twelve patients (13%) had stable disease, and the remaining twenty‐six (27%) had progressive disease as their best response. At a median follow‐up of 11.5 months, median progression‐free survival and overall survival were 8 and 26.5 months, respectively. Multivariate analysis showed that chemosensitivity to treatment administered before BV was associated with a significantly increased probability of achieving response to BV ( P  = .005). Bulky disease ( P  = .01) and response to BV ( P  <.001) were significant for progression‐free survival, while refractoriness to most recent treatment ( P  = .04), bulky disease ( P  = .005), and B‐symptoms ( P  = .001) were unfavorable factors for overall survival. Among the 22 CRs, 5 remain in CR with no further treatment after BV at a median follow‐up of 13 months. In conclusion, our data indicate that BV is an effective treatment for R/R HL patients even outside clinical trials. Whether BV can cure a fraction of patients remains to be seen.